Klestadt′s cyst: A rarity - Patil Karthikeya; Mahima V; Divya A (Wolters Kluwer Medknow Publications, 2007)
Klestadt′s cyst, more commonly known as the nasolabial cyst is an uncommon, non-odontogenic, soft tissue cyst characterized by its extra osseous location in the nasal alar region.[2] Following its description first by Zukuerkandl in 1882,[3] only 267 cases have been found in English literature. A case of nasolabial cyst in a 30-year-old female patient is presented.